2002
DOI: 10.1021/jf0204203
|View full text |Cite
|
Sign up to set email alerts
|

Nonenzymatic Antioxidant Activity of Four Organosulfur Compounds Derived from Garlic

Abstract: The nonenzymatic antioxidant activity of diallyl sulfide (DAS), diallyl disulfide (DADS), S-ethyl cysteine (SEC), and N-acetyl cysteine (NAC) in the liposome system was examined. The antioxidant protection from these organosulfur agents was concentration dependent (p < 0.05). SEC and NAC showed significantly lower lipophilicity and greater reducing power than DAS and DADS (p < 0.05). Greater antioxidant protection was presented in the combinations of alpha-tocopherol with four organosulfur agents than alpha-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
0
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 26 publications
7
70
0
7
Order By: Relevance
“…For example, polysulfide compounds (i.e., DATS) have previously been shown to be antioxidants and modify thiol proteins (41,42). It is possible that some of the effects of DATS that we observed are independent of H 2 S release and are a result of DATS-mediated protein modifications.…”
Section: Discussionmentioning
confidence: 71%
“…For example, polysulfide compounds (i.e., DATS) have previously been shown to be antioxidants and modify thiol proteins (41,42). It is possible that some of the effects of DATS that we observed are independent of H 2 S release and are a result of DATS-mediated protein modifications.…”
Section: Discussionmentioning
confidence: 71%
“…Reducing capacity of Allium extracts was not investigated, however, high antioxidant activity of red onion scales (Velioglu et al, 1998) and garlic (Yin and Cheng, 1998) was reported. Non-enzymatic antioxidant activity of garlic extract was also reported by Yin et al (2002). However, according to some authors (Amagase et al, 2001;Imai et al, 1994), this antioxidant activity (AOX) was more attributed to the organosulfur compounds.…”
Section: Total Phenolicsmentioning
confidence: 73%
“…IAAs have no effects on the radical scavenge activity of α-tocopherol and BHT. These results showed that sulfhydryl compounds containing thiol groups in garlic, maybe diallyl trisulfide, are responsible for part of the ABTS radical scavenging activity of garlic [23]. Figure 7.…”
Section: Reducing Powermentioning
confidence: 90%